Analysis of Language Errors in Indonesian Expository Essays by Junior High School Students - Rahman, Muhammad Ali; Sulistyono, Yunus (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This research aims to identify and describe forms of language errors in the areas of phonology, morphology and syntax in the expository text essays of students at SMP N 4 Karanganom. Methodology: The method used in this research is descriptive qualitative. The data in this research are expository text essays from class VIII A students of SMP N 4 Karanganom. Data collection techniques include observation and documentation by collecting expository text essays from class VIII A students of SMP N 4 Karanganom. The data analysis technique in this research uses tapping techniques and advanced free-to-engage listening techniques. Results: Based on the results of the analysis, errors were found at the phonological level, such as errors in the use of capital letters, errors in the use of punctuation marks, and errors in combining words. At the morphological level, errors were found in using the suffix -an, writing the prefix me-, writing the prefix ber-, writing a combination of the prefix di- with the suffix -kan, and errors in writing prepositions. Meanwhile, at the syntactic level, errors were found in unclear sentences and the use of redundant words. Applications/Originality/Value: The findings of this research can be used as a reference for teachers to design more effective language learning activities that focus on minimizing phonological, morphological, and syntactic errors in students’ writing.